The The Effect Of Presentation Practice Production (Ppp) Technique On Student’s English Grammar Competence By Using Computer Assisted Language Learning - Siregar, Putri Delima (Pascasarjana Universitas HKBP Nommensen, 2021)
This study deals with the effect of presentation practice production on students’ English grammar competence by using computer assisted language learning. The objective of this thesis is to find out the effect of presentation practice production on students’ English grammar competence by using computer assisted language learning. This study is an experimental research. The population of this study is the student class of X of SMK Parulian 1 MEDAN. The number of students was 100 students. 40 students are taken as the sample. The first group is experimental group which is teach by applying presentation practice production technique on computer assisted language learning. While the second group is control group, it is teach without presentation practice production technique on computer assisted language learning. Multiple choice test is used, as the instrument for collecting the data. These test consisted of two types, namely pre-test and post-test. As the result of the test, t-observed was 3.14 and t-table was 1.686 (p:005) the result of the data analysis show that the value of t-table 3.14 1.686(p:0.05). It means that hypothesis alternative (Ha) is accepted while the null hypothesis (Ho) is rejected, therefore it is concluded that presentation practice production technique on computer assisted language learning significantly affects students’ English grammar competence. Based on the explanation above, this research can be chosen as one alternative in teaching learning process.